Medical assisting - Keir, Lucille Q
Includes bibliographical references and index.; This competency-based learning system covers the administrative, clinical, and general areas necessary for entry-level employment as identified by the medical assistant role delineation study issued by the American Association of Medical Assistants. A listing of role delineation areas in each unit and in Appendix A make it easy to locate specific skills within each competency. A unit on related therapies presents information on complimentary and alternative treatments.